Force of fire - DasGupta, Sayantani (DasGupta, Sayantani. Kiranmala and the kingdom beyond, 2021)
A descendent from a long line of demons who build interspecies relationships to fight tyranny works competitively to control her dangerous fire-breathing skills, before a Serpentine Governor's charming son enlists her help to defeat a growing rebellion.